Injuries in girls' soccer and basketball: a comparison of high schools with and without athletic trainers - Lauren A. Pierpoint; Cynthia R. LaBella; Christy L. Collins; Sarah K. Fields; R. Dawn Comstock (BMC, 2018)
Abstract Background Sports injuries impose physical and economic burdens on high school athletes, yet only 37% of high schools have access to a fulltime certified athletic trainer (AT). Although intuitively there are multiple benefits of AT coverage, research demonstrating the measurable effect of AT coverage on rates and patterns of injury is limited. Our objective was to investigate the epidemiology of girls' basketball and soccer injuries in high schools with and without an AT. Methods We compared data captured by two similar sports injury surveillance systems during the 2006/07-2008/09 academic years. High School Reporting Information Online (RIO) included a national sample of schools with ATs, and the Sports Injury Surveillance System (SISS) included a sample of Chicago public high schools without ATs. Results Overall injury rates were higher in schools without ATs than schools with ATs in girls' soccer (RR: 1.73, 95% CI: 1.51-2.00) and basketball (RR: 1.22, 95% CI: 1.03-1.45). Recurrent injury rates were even higher in schools without ATs compared to schools with ATs in soccer (RR: 6.00 95% CI: 4.54-7.91) and basketball (RR: 2.99, 95% CI: 2.12-4.14). Conversely, concussion rates were higher in schools with ATs than schools without ATs in soccer (RR: 8.05, 95% CI: 2.00-32.51) and basketball (RR: 4.50, 95% CI: 1.43-14.16). Other injury patterns were similar between the two samples. Conclusions This study demonstrated the effectiveness of AT coverage of high school girls' soccer and basketball, both in reducing overall and recurrent injury rates and in identifying athletes with concussions. Future studies should evaluate the effect of ATs on other high school sports and on youth sports to determine if these findings are generalizable across sports and age groups.